Discharge performance of blended salt in matrix materials for low enthalpy thermochemical storage - Eifion Jewell (Applied Thermal Engineering, 2018)
A novel study is undertaken on low cost thermochemical storage which utilizes temperatures which are compatible with low grade renewable energy capture. The discharge performance of thermochemical storage matrix materials is assessed using a custom developed experimental apparatus which provides a means of comparing materials under scaled reactor conditions. The basic performance of three salts (CaCl2, LiNO3 and MgSO4) was investigated and their subsequent performance using layering and blending techniques established that the performance could be increased by up to 24% through the correct choice of mixing technique. Layering the CaCl2 on the LiNO3 provided the most efficient thermal release strategy and yielded a thermal storage density of 0.2 GJ/m3. The research also uniquely highlights the important finding that incorrect mixing of the materials can lead to a significant reduction in efficiency with freely mixed CaCl2 and LiNO3 possessing a storage capacity of less than 0.01 GJ/m3 as a result of chemical interactions between the deliquesced materials in close proximity. The paper has impact for the design and control of thermochemical storage systems as it clearly identifies how performance can be improved or degraded by the choice and the structuring of the materials.